Pengaruh Alertness Entrepreneurship Dan Penghasilan Orang Tua Terhadap Intensi Berwirausaha Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Negeri Padang - Rusmana, Sonya; Rahmi, Elvi (Jurnal Salingka Nagari, 2024)
This research seeks to examine the relationship between Alertness Entrepreneurship and Parental Income as it pertains to the entrepreneurial aspirations of Economics and Business Faculty students, Universitas Negeri Padang. Based on initial observations, students tend to choose seeking employment after graduation rather than becoming entrepreneurs. Entrepreneurial intention is a strong desire to engage in entrepreneurial activities, backed by a variety of internal and external variables, including as Alertness Entrepreneurship and Parental Income. Using the Slovin formula and the purposive sampling approach, a sample size of 100 was calculated for the research, which covered a population of 3,001 pupils. Questionnaires served to collect information that was subsequently evaluated with descriptive statistics and multiple linear regression. Both Alertness Entrepreneurship and Parental Income significantly impact entrepreneurial inclinations, according to the data. With an adjusted R-squared value of 0.410, these two variables account for 41% of the variation in entrepreneurial ambitions, however the remaining 59% are affected by other factors that are not covered in this research.